2020
DOI: 10.1371/journal.pone.0238952
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a customizable training environment for neurointerventional skills assessment

Abstract: Objective To meet increasing demands to train neuroendovascular techniques, we developed a dedicated simulator applying individualized three-dimensional intracranial aneurysm models ('HANNES'; Hamburg Anatomic Neurointerventional Endovascular Simulator). We hypothesized that HANNES provides a realistic and reproducible training environment to practice coil embolization and to exemplify disparities between neurointerventionalists, thus objectively benchmarking operators at different levels of experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Although they had a small sample size, a significant effect was found. Two of the three in vitro studies included medical students as study subjects [ 21 , 22 ], whereas the other two studies compared interventional radiologists [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they had a small sample size, a significant effect was found. Two of the three in vitro studies included medical students as study subjects [ 21 , 22 ], whereas the other two studies compared interventional radiologists [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies covering the effect of simulator training on AEs in IR were identified in this review. A small analysis of neurointerventional skills in simulator training reported significantly more dangerous manoeuvres by inexperienced operators than experienced ones [ 20 ]. Simulators give the chance to analyse and specifically reduce such dangerous procedures before performing them on patients.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report on neurointerventional simulation training showed that the training effects for neurointervention-experienced operators are not as marked when compared to inexperienced operators. 18) In addition, most of the reports focus on the training effects on medical students or residents. From these, it was hypothesized that neurointerventional simulation training for experts was not popular.…”
Section: Discussionmentioning
confidence: 99%
“…The use of 3D-printed patient-specific models of intracranial aneurysms enable the neurointerventionalist to plan and perform in vitro the endovascular embolization with the possibility to test different strategies with different sizes and landing zones for the embolization devices [13][14][15]. The patient can thus benefit from the increased confidence of the neurointerventionalist who will have already performed the in vitro endovascular intervention and integrated each step.…”
Section: Introductionmentioning
confidence: 99%